Vasculitis and organ pathology: a practical approach to histological diagnosis and clinical-pathologic correlations. - Giordano, Carla; d’Amati, Giulia (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2024)
Vasculitides are a complex and pleomorphic group of diseases, involving all types of vessels and, potentially, all organs, with heterogeneous clinical manifestations. The clinical diagnosis can be challenging due to the diverse clinical manifestations, variable disease course, and overlapping features with other conditions. Overall, the histopathologic diagnosis is a crucial component in the clinical workup and plays a central role in guiding treatment decisions and prognosis estimation. However, reaching a diagnosis can be challenging, due to the complexity of the disease, and the variability in histological findings of these disorders, often caused by the development of secondary changes that may obscure the diagnostic features. Moreover, vasculitides are relatively rare, and many pathologists are unfamiliar with the disease and their diagnostic criteria, both in the biopsy and autopsy setting. This monographic issue collects papers focused on the updated classification of vasculitis, recommendations for sample histologic processing, and clues to the histopathologic diagnosis in diverse organs and systems, providing a practical approach to this complex disease. We also want to take this opportunity to honor the memory of our friend and colleague G. Rossi with the editorial written by some of his best friends. His great commitment as a pathologist and as a researcher, his personality, full of generous outbursts, and his ability to put himself completely at the service of the institutions in which he served professionally, are a legacy that helps all of us in our daily lives and professions.